The Subversion of the Immune System by Francisella Tularensis - Bosio, Catharine (Frontiers in Microbiology, 2011)
Francisella tularensis is a highly virulent bacterial pathogen and the causative agent of tularemia. Perhaps the most impressive feature of this bacterium is its ability to cause lethal disease following inoculation of as few as 15 organisms. This remarkable virulence is, in part, attributed to the ability of this microorganism to evade, disrupt and modulate host immune responses. The objective of this review is to discuss the mechanisms utilized by F. tularensis to evade and inhibit innate and adaptive immune responses. The capability of F. tularensis to interfere with developing immunity in the host was appreciated decades ago. Early studies in humans were the first to demonstrate the ability of F. tularensis to suppress innate immunity. This work noted that humans suffering from tularemia failed to respond to a secondary challenge of endotoxin isolated from unrelated bacteria. Further, anecdotal observations of individuals becoming repeatedly infected with virulent strains of F. tularensis suggests that this bacterium also interferes with the generation of adequate adaptive immunity. Recent advances utilizing the mouse model for in vivo studies and human cells for in vitro work have identified specific bacterial and host compounds that play a role in mediating ubiquitous suppression of the host immune response. Compilation of this work will undoubtedly aid in enhancing our understanding of the myriad of mechanisms utilized by virulent F. tularensis for successful infection, colonization and pathogenesis in the mammalian host.